Educational psychology : windows on classrooms - Eggen, Paul D. , 1940-; Kauchak, Donald P. , 1946- (Peason, 2013)
Educational Psychology: Windows on Classrooms, Ninth Edition, will help you increase student learning and development. It is the most applied book in the field. If you're looking for a book that gives you a sound theoretical and research-based foundation and then provides specific and concrete illustrations and guidelines for applying this theory and research with your students, this is the book for you